2019
DOI: 10.2147/ijn.s194192
|View full text |Cite
|
Sign up to set email alerts
|

<p>Antioxidant and toxicity studies of biosynthesized cerium oxide nanoparticles in rats</p>

Abstract: Purpose The purpose of this study was to investigate the acute toxic potential of cerium oxide nanoparticles (CNPs) synthesized by pullulan in adult male Wistar rats. Patients and methods Thirty male Wistar rats randomly were divided into five experimental groups of six animals each. The animals were received 50, 100, 200, and 400 mg/kg CNPs for 14 consecutive days. At the end of the experiment, the rats were euthanized and histopathological evaluation of the liver and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 57 publications
3
24
0
1
Order By: Relevance
“…There are many different studies that have con rmed the antioxidant properties of CeONPs in different tissues and in serum [39][40][41]. In a study by Kim et al in 2017, they showed under conditions similar to our experiment, that injection of the same amount of CeONPs could reduce the ROS levels at the lesion site after SCI.…”
Section: Discussionsupporting
confidence: 80%
“…There are many different studies that have con rmed the antioxidant properties of CeONPs in different tissues and in serum [39][40][41]. In a study by Kim et al in 2017, they showed under conditions similar to our experiment, that injection of the same amount of CeONPs could reduce the ROS levels at the lesion site after SCI.…”
Section: Discussionsupporting
confidence: 80%
“…These peculiar chemical and physical features make CeO 2 -NPs a promising and exciting compound for biomedical applications. This is further favoured by the absence of toxicity in several tissues as demonstrated by multiple studies either in vitro and in vivo [ 151 ]. Nonetheless, some data indicate a certain degree of citotoxicity and therefore further study is needed to deepen the biocompatibility of CeO 2 -NPs [ 152 ].…”
Section: Nanoceria: a New Nanotechnology Approach To Combat Amd-inmentioning
confidence: 99%
“…Inorganic nanoparticles suitable for nanomedicine include gold [110][111][112][113][114] and silver [115,116] nanoparticles, cerium dioxide [117,118], silica [119,120], as well as inorganic salts [121][122][123].…”
Section: Inorganic Particlesmentioning
confidence: 99%